IMPROVING THE KNOWLEDGE OF BREASTFEEDING MOTHERS IN PROVIDING BREASTFEEDING IN PAGERWESI VILLAGE, TRUCUK DISTRICT, BOJONEGORO REGENCY: PENINGKATAN PENGETAHUAN IBU MENYUSUI, DALAM PEMBERIAN ASI DI DESA PAGERWESI, KEC. TRUCUK, KAB BOJONEGORO - Rahmawati, Andin Ajeng; Hariastuti, S.ST., M.Kes., Fela; Saraswati, S.ST., M.Kes., Devi (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2025)
The World Health Organization (WHO) recommends that all infants be exclusively breastfed (i.e., receive only breast milk and no other food or drink) for the first 6 months of life to achieve optimal growth, development, and health. Infants should start receiving complementary foods at 6 months, while breastfeeding should continue until 2 years of age. Exclusive breastfeeding until 6 months and continued breastfeeding until 2 years helps reduce infant mortality and morbidity, lower the risk of necrotizing enterocolitis, reduce the risk of allergic diseases, obesity, type II diabetes, hypertension, and hypercholesterolemia later in life. Despite the abundance of evidence on the benefits of exclusive breastfeeding, rates of exclusive breastfeeding remain low in both developed and developing countries. Globally, less than 40% of infants under 6 months are exclusively breastfed. This program starts with the first visit, conducting a physical examination of the breastfeeding mother, a psychological assessment of the breastfeeding mother, an intensive family assessment, and providing midwifery care tailored to the breastfeeding mother's condition. This is one of the efforts of the PkM team to help minimize the risks for breastfeeding mothers and ensure optimal infant growth and development. The fifth meeting involves implementing the results of the assessment through activities such as teaching breast care and proper breastfeeding techniques. The final meeting evaluates the overall success of the program. This family support program aims to determine the extent to which families can handle existing health problems. One of the issues addressed is related to exclusive breastfeeding among breastfeeding mothers. Therefore, the PkM team provides interventions in the form of breast care and proper breastfeeding techniques.